2015
DOI: 10.1002/cssc.201501036
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Partial Oxidation of Lignin to Carboxylic Acids over Vanadium Pyrophosphate and Aluminum–Vanadium–Molybdenum

Abstract: Lignin is a complex polymer that is a potential feedstock for aromatic compounds and carboxylic acids by cleaving the β-O-4 and 5-5' linkages. In this work, a syringe pump atomizes an alkaline solution of lignin into a catalytic fluidized bed operating above 600 K. The vanadium heterogeneous catalysts convert all the lignin into carboxylic acids (up to 25 % selectivity), coke, carbon oxides, and hydrogen. Aluminum-vanadium-molybdenum mostly produced lactic acid (together with formic acid, acrylic acid, and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 43 publications
(89 reference statements)
0
32
0
Order By: Relevance
“…17 Overview of the oxidative lignin depolymerisation methods: alkaline oxidation to phenolics, 112,113,180,338, acidic/pH-neutral oxidation to phenolics, [474][475][476][477][478][479][480][481][482][483][484][485][486][487] and oxidation to non-phenolic carboxylic acids. 179,[488][489][490][491] The yield histograms indicate the relative distribution of maximum reported monomer yields for each depolymerisation study and for each lignin substrate (if multiple substrates were used). The process characteristics and monomer yields of each individual study can be found in the ESI † (Tables S6-S8).…”
Section: Depolymerisation Of Isolated Ligninmentioning
confidence: 99%
“…17 Overview of the oxidative lignin depolymerisation methods: alkaline oxidation to phenolics, 112,113,180,338, acidic/pH-neutral oxidation to phenolics, [474][475][476][477][478][479][480][481][482][483][484][485][486][487] and oxidation to non-phenolic carboxylic acids. 179,[488][489][490][491] The yield histograms indicate the relative distribution of maximum reported monomer yields for each depolymerisation study and for each lignin substrate (if multiple substrates were used). The process characteristics and monomer yields of each individual study can be found in the ESI † (Tables S6-S8).…”
Section: Depolymerisation Of Isolated Ligninmentioning
confidence: 99%
“…Highly exothermic or endothermic processes, explosive reactions, and vapourizing/reacting liquid streams are more challenging in fixed beds compared to fluidized beds. Atomizing non‐volatile compounds—fructose, xylose, vegetable oil, lignin, glycerol, and bitumen—through spargers into micro‐fluidized beds requires high gas velocities (50.33emnormalm0.25em0.25ems1 to 200.33emnormalm0.25em0.25ems1), which attrit even supported catalysts. Heating the gas to reaction conditions is a limiting factor, and so solids backmixing and higher gas velocities heat the atomized droplets faster.…”
Section: Uncertaintymentioning
confidence: 99%
“…We present how to reduce uncertainty with methodical design algorithms and guidelines to select reactor types and geometry. Other articles as part of this special series on experimental methods in chemical engineering, discuss thermogravimetric analysis and small fixed and fluidized beds to estimate intrinsic fluid‐solid reaction kinetics …”
Section: Descriptionmentioning
confidence: 99%